2020
DOI: 10.1016/j.pan.2020.05.003
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 presenting as acute pancreatitis

Abstract: The ongoing pandemic of Coronavirus disease-2019 (COVID-19) has spread over 200 countries worldwide, affecting >2 million people and >120,000 deaths. COVID-19 is caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). The most common symptoms include cough, shortness of breath, and fever. However, gastrointestinal manifestations of COVID-19 are increasingly being recognized. Herein, we report a case of COVID-19 who presented with acute pancreatitis (AP) without any other risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
193
0
24

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(221 citation statements)
references
References 6 publications
(6 reference statements)
4
193
0
24
Order By: Relevance
“…Besides various autoinflammatory/autoimmune conditions ( Rodríguez et al, 2020 ), a couple of recent observations have also evinced potential diabetogenic effect of COVID-19 ( Aloysius et al, 2020 ; Ren et al, 2020 ; Rubino et al, 2020 ). Attributable to the tropism of SARS-CoV-2 for the pancreatic β-cells and impairment of their function in concert with the cytokine storm and counter-regulatory hormonal responses, new-onset diabetes besides severe metabolic complications of preexisting diabetes, including diabetic ketoacidosis and hyperosmolarity could set in patients with COVID-19 ( Aloysius et al, 2020 ; Ren et al, 2020 ; Rubino et al, 2020 ). On the other hand, worse consequences are observed in COVID-19 patients presented with diabetes, bracketed together with a range of associated conditions augmenting the risk ( Apicella et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides various autoinflammatory/autoimmune conditions ( Rodríguez et al, 2020 ), a couple of recent observations have also evinced potential diabetogenic effect of COVID-19 ( Aloysius et al, 2020 ; Ren et al, 2020 ; Rubino et al, 2020 ). Attributable to the tropism of SARS-CoV-2 for the pancreatic β-cells and impairment of their function in concert with the cytokine storm and counter-regulatory hormonal responses, new-onset diabetes besides severe metabolic complications of preexisting diabetes, including diabetic ketoacidosis and hyperosmolarity could set in patients with COVID-19 ( Aloysius et al, 2020 ; Ren et al, 2020 ; Rubino et al, 2020 ). On the other hand, worse consequences are observed in COVID-19 patients presented with diabetes, bracketed together with a range of associated conditions augmenting the risk ( Apicella et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…When looking at extra-vascular ndings, clinical events included ventilation-related complications like pneumothorax and pneumomediastinum only in a small proportion of ICU cases. Acute pancreatitis, that Aloysius et al have reported as COVID-19 presenting event [28], was also detected in 3 ICU cases thus allowing clinicians to start targeted therapies.…”
Section: Discussionmentioning
confidence: 98%
“…The most common symptoms in COVID-19 are fever and respiratory symptoms, followed by GI symptoms such as diarrhea, vomiting, anorexia, dysgeusia, and abdominal pain [ 4 , 56 - 59 ]. Based on the SECURE-IBD registry-based study, about 30% of the patients reported an increase in baseline IBD symptoms [ 55 ].…”
Section: Gi Manifestations Of Covid-19mentioning
confidence: 99%